Contribution of Zinc Solubilizing Bacteria in Growth Promotion and Zinc Content of Wheat - Kamran, Sana; Shahid, Izzah; Baig, Deeba N.; Rizwan, Muhammad; Malik, Kauser A.; Mehnaz, Samina (Frontiers in Microbiology, 2017)
Zinc is an imperative micronutrient required for optimum plant growth. Zinc solubilizing bacteria are potential alternatives for zinc supplementation and convert applied inorganic zinc to available forms. This study was conducted to screen zinc solubilizing rhizobacteria isolated from wheat and sugarcane, and to analyze their effect on wheat growth and development. Fourteen exo-polysaccharides producing bacterial isolates of wheat were identified and characterized biochemically as well as on the basis of 16S rRNA gene sequences. Along these, ten identified sugarcane isolates were also screened for zinc solubilizing ability on five different insoluble zinc sources. Out of twenty four, five strains, i.e., EPS 1 (Pseudomonas fragi), EPS 6 (Pantoea dispersa), EPS 13 (Pantoea agglomerans), PBS 2 (E. cloacae) and LHRW1 (Rhizobium sp.) were selected (based on their zinc solubilizing and PGP activities) for pot scale plant experiments. ZnCO3 was used as zinc source and wheat seedlings were inoculated with these five strains, individually, to assess their effect on plant growth and development. The effect on plants was analyzed based on growth parameters and quantifying zinc content of shoot, root and grains using atomic absorption spectroscopy. Plant experiment was performed in two sets. For first set of plant experiments (harvested after one month), maximum shoot and root dry weights and shoot lengths were noted for the plants inoculated with Rhizobium sp. (LHRW1) while E. cloacae (PBS 2) increased both shoot and root lengths. Highest zinc content was found in shoots of E. cloacae (PBS 2) and in roots of P. agglomerans (EPS 13) followed by zinc supplemented control. For second set of plant experiment, when plants were harvested after three months, Pantoea dispersa (EPS 6), P. agglomerans (EPS 13) and E. cloacae (PBS 2) significantly increased shoot dry weights. However, significant increase in root dry weights and maximum zinc content was recorded for Pseudomonas fragi (EPS 1) inoculated plants, isolated from wheat rhizosphere. While maximum zinc content for roots was quantified in the control plants indicating the plant’s inability to transport zinc to grains, supporting accelerated bioavailability of zinc to plant grains with zinc solubilizing rhizobacteria.